Cardiomyopathy Disease of the Heart Muscle - Mattsson, Gustav; Magnusson, Peter (IntechOpen, 2021)
Cardiomyopathies are diseases of the heart muscle with diverse etiologies ranging from myocarditis to gene mutations. They are classified according to morphology and function, and then further categorized based on whether they are familial or non-familial and based on specific etiologies. This book examines the various cardiomyopathies, including arrhythmogenic cardiomyopathy, hypertrophic cardiomyopathy, and dilated cardiomyopathy, as well as their genetic basis.